2013
DOI: 10.1007/s00464-013-3277-9
|View full text |Cite
|
Sign up to set email alerts
|

Revised sleeve gastrectomy: another option for weight loss failure after sleeve gastrectomy

Abstract: The ReSG may be a valid option for failure of primary LSG for both primary or secondary dilatation. Long-term results of ReSG are awaited to prove efficiency. Further prospective clinical trials are required to compare the outcomes of ReSG with those of Roux en Y Gastric Bypass or DS for weight loss failure after LSG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 20 publications
2
57
1
2
Order By: Relevance
“…Marceau et al reported excellent 20 years results after BPD-DS with a %EWL of over 70% [3], but Biron et al mentioned that weight regains after BPD-DS is an increasing problem, especially in super-obese patients, doubling the failure rate every five years with weight regain [16]. In our series, we identified 17 patients with weight regain at a median follow-up of more than 5 years In bariatric surgery, weight regain is a common problem [7,17,18]. Even after satisfactory weight loss, weight regain can occur if patients go back to bad eating habits and sedentary lifestyle [8,19].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Marceau et al reported excellent 20 years results after BPD-DS with a %EWL of over 70% [3], but Biron et al mentioned that weight regains after BPD-DS is an increasing problem, especially in super-obese patients, doubling the failure rate every five years with weight regain [16]. In our series, we identified 17 patients with weight regain at a median follow-up of more than 5 years In bariatric surgery, weight regain is a common problem [7,17,18]. Even after satisfactory weight loss, weight regain can occur if patients go back to bad eating habits and sedentary lifestyle [8,19].…”
Section: Discussionmentioning
confidence: 88%
“…In SG, Baltasar et al reported first on two patients who had undergone re-SG for dilation of SG, with subsequent increased successive weight loss [23]. Other authors reported comparable observation with a substantial of weight regain in up to 23% of SG [5,6,11,18]. However, consideration should be given to a possible re-SG since additional gastric volume restriction might jeopardize the patient's psychological balance [8].…”
Section: Discussionmentioning
confidence: 99%
“…examples include SG, RYGB, and AGB [8,9,11,12]. Conversion operations to RYGB (CRYGB) have been reported to be feasible and well tolerated after failed AGB [12].…”
Section: Discussionmentioning
confidence: 99%
“…Other reports demonstrated that both CSG and CRYGB were feasible options and resulted in further substantial weight loss [8]. Another study revealed that CSG might be a valid option for managing PSG complications such as primary or secondary dilatation [11]. However, there is still insufficient evidence to help establish robust guidelines for conversion operations after failed primary bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation